2015
DOI: 10.1515/jpem-2014-0417
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for pediatric craniopharyngiomas: is less more?

Abstract: Surgery for craniopharyngiomas, especially in childhood and adolescence, has evolved from an era of aggressive strategies - with the primary goal of gross total removal and accepting an impaired functional outcome - to a more individually tailored therapy that avoids immediate treatment-related and long-term morbidity. Modern imaging techniques and a wider understanding of hypothalamic risk factors have led to surgical strategies adapted to the localization of these inhomogenously grown pathologies. Whereas pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Historically, transcranial, supraorbital, or transsphenoidal approaches have been employed based upon location and extent of tumor 71,78 . Improvements in endoscopic and microsurgical resection techniques, as well as planned subtotal resection with adjuvant radiotherapy, may further diminish morbidity 77,79‐81 …”
Section: Craniopharyngiomasmentioning
confidence: 99%
“…Historically, transcranial, supraorbital, or transsphenoidal approaches have been employed based upon location and extent of tumor 71,78 . Improvements in endoscopic and microsurgical resection techniques, as well as planned subtotal resection with adjuvant radiotherapy, may further diminish morbidity 77,79‐81 …”
Section: Craniopharyngiomasmentioning
confidence: 99%
“…For favourably localized tumours, the preferred treatment of choice, especially at primary craniopharyngioma diagnosis, is an attempt at complete resection with preservation of visual and hypothalamic function [ 6 ▪ , 12 , 39 , 45 50 ]. For unfavourably localized tumours – those too close to or too entangled with the optic chiasm and/or the hypothalamus – a planned limited resection should be performed to preserve integrity of and/or to avoid further damage to the hypothalamic and optic structures [ 4 ▪ , 51 ▪ , 52 , 53 , 54 ▪▪ , 55 ▪ 57 ▪ ]. Endoscopic routes provide novel and less traumatic approaches for surgical resection [ 58 ▪ , 59 ].…”
Section: Treatment Strategies and Hypothalamic Injurymentioning
confidence: 99%
“…Associated with high morbidity, suprachiasmatic lesions are difficult to treat. Surgical removal of tumour tissue beyond the mammillary bodies risks hypothalamic structures and consequent hypothalamic obesity [ 39 , 40 , 51 ▪ , 73 ▪ ]. With the aid of imaging studies, recent reports have indicated that the degree of obesity of affected patients is positively correlated with the degree of hypothalamic damage [ 39 , 40 42 ▪ ].…”
Section: Hypothalamic Obesitymentioning
confidence: 99%
See 1 more Smart Citation